PERENCANAAN DAN PENINGKATAN KEUANGAN MELALUI INVESTASI DIGITAL SYARIAH PADA MASYARAKAT DI KAWASAN CAGAR BUDAYA KERATON KARTASURA - Kusuma, Melia; Nurohman, Yulfan Arif; Yahya, Alvin (Sekolah Tinggi Ilmu Ekonomi AMA, 2024)
Family economic welfare is everyone's hope. Economic welfare can be successful if there are right decisions in managing finances that begin with financial planning and decisions. The role of housewives and women in economic welfare can be shown in financial management, so a good understanding is needed in managing finances. This community service program aims to improve understanding of financial planning and improvement through digital investment. The participants of the method used through Asset Based Community Development (ABCD) with housewives and women in the cultural heritage area of the Kartasura palace. The results of the training provided will encourage participants to have appropriate digital investment planning and decisions, so that in the future they can obtain welfare